Entertainment law - Helewitz, Jeffrey (Thomson, 2004)
Entertainment Law was written with the reader in mind. Complex legal principles are presented in language that is easily understood and are portrayed using a host of interesting case examples. The edited judicial decisions, showing court interpretation, make this book unlike any other currently on the market.